2014
DOI: 10.5901/mjss.2014.v5n27p1530
|View full text |Cite
|
Sign up to set email alerts
|

Identity Statuses Scale in EFL Settings: A Case of Formal and Informal Contexts

Abstract: The considerable literature on identity formation as the critical basis of individuals' wellbeing made the researchers design a delicate Identity Statuses Scale (ISS) inspired by Marcia's (1966)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Through Principle Component Analysis, they found four interrelated factors: religious identity, social interpersonal identity, cultural identity, and political identity. Sayah et al (2014) also found that the participants obtained a higher score in perceiving the four statues in English institutes compared to public schools. Moreover, the study revealed that English institute’s students were moratorium and identity achievers at social interpersonal construct compared to public schools.…”
Section: Identity and Psychosociologymentioning
confidence: 74%
See 1 more Smart Citation
“…Through Principle Component Analysis, they found four interrelated factors: religious identity, social interpersonal identity, cultural identity, and political identity. Sayah et al (2014) also found that the participants obtained a higher score in perceiving the four statues in English institutes compared to public schools. Moreover, the study revealed that English institute’s students were moratorium and identity achievers at social interpersonal construct compared to public schools.…”
Section: Identity and Psychosociologymentioning
confidence: 74%
“…In that case, the event can result in a reappraisal of previously held beliefs, either going back to the former position or upgrading to a new one as he adopts new values. Inspired by Marcia’s (1966) identity statuses, Sayah et al (2014) validated the identity scale by running Structural Equation Modeling (SEM). They examined the participants’ age, gender, and school differences across two contexts (English institutes and public schools).…”
Section: Identity and Psychosociologymentioning
confidence: 99%